Effects of a randomized controlled intervention trial on return to work and health care utilization after long-term sickness absence. (December 2016) - Momsen, Anne-Mette; Stapelfeldt, Christina; Nielsen, Claus; Nielsen, Maj; Aust, Birgit; Rugulies, Reiner; Jensen, Chris
Abstract Background The aim of the RCT study was to investigate if the effect of a multidisciplinary intervention on return to work (RTW) and health care utilization differed by participants' self-reported health status at baseline, defined by a) level of somatic symptoms, b) health anxiety and c) self-reported general health. Methods A total of 443 individuals were randomized to the intervention (n = 301) or the control group (n = 142) and responded to a questionnaire measuring health status at baseline. Participants were followed in registries measuring RTW and health care utilization. Relative risk (RR) and odds ratio (OR) were used as measures of associations. Results were adjusted for gender, age, educational level, work ability and previous sick leave. Results Among all responders we found no effect of the intervention on RTW. Among participants with low health anxiety, the one-year probability of RTW was lower in the intervention than in the control group (RR = 0.79 95 % CI 0.68-0.93), but for those with high health anxiety there was no difference between the groups (RR = 1.15 95 % CI 0.84-1.57). Neither general health nor somatic symptoms modified the effect of the intervention on RTW. The intervention had no effect on health care utilization. Conclusions The multidisciplinary intervention did not facilitate RTW or decrease health care utilization compared to ordinary case management in subgroups with multiple somatic symptoms, health anxiety or low self-rated health. However, the intervention resulted in a reduced chance of RTW among participants with low health anxiety levels. Trial registration ISRCTN43004323, andISRCTN51445682